2016
DOI: 10.1080/15384047.2016.1235658
|View full text |Cite|
|
Sign up to set email alerts
|

Chk1 and DNA-PK mediate TPEN-induced DNA damage in a ROS dependent manner in human colon cancer cells

Abstract: Recently, we showed that the metal chelator TPEN targets colon cancer cells through redox cycling of copper. Here, we studied the DNA damage potential of TPEN and deciphered the role of Chk1, ATM and DNA-PK in TPEN-induced toxicity in 3 human colon cancer cell lines, HCT116, SW480 and HT29. We also investigated the role of reactive oxygen species (ROS) in TPEN-induced DNA damage. TPEN reduced cell viability in a dose-and time-dependent manner. Cytotoxicity was associated with significant DNA damage and higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Apoptosis induced by zinc depletion is recognized as a potential therapeutic strategy for cancer (Cui et al, 2014;Li et al, 2009). The apoptotic effects of zinc chelator TPEN have been reported on several types of cells, including colon cancer cells and acute promyelocytic leukemia cells (Gurusamy et al, 2011;Rahal et al, (Fatfat et al, 2014;Rahal et al, 2016). However, in acute lymphoblastic leukemia cells, TPENinduced cell apoptosis was not correlated with its zinc chelation activity.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis induced by zinc depletion is recognized as a potential therapeutic strategy for cancer (Cui et al, 2014;Li et al, 2009). The apoptotic effects of zinc chelator TPEN have been reported on several types of cells, including colon cancer cells and acute promyelocytic leukemia cells (Gurusamy et al, 2011;Rahal et al, (Fatfat et al, 2014;Rahal et al, 2016). However, in acute lymphoblastic leukemia cells, TPENinduced cell apoptosis was not correlated with its zinc chelation activity.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to mimic zinc deficiency in vitro using TPEN and determine the effect of Zn depletion on DENV infection. Many previous studies have shown around 70-80% depletion in labile Zn levels using high concentrations of TPEN for short duration (37,38). We first measured the effect of increasing concentrations of TPEN on cell proliferation.…”
Section: Zinc Chelation Specifically Inhibits Flavivirus Infectionmentioning
confidence: 99%
“…With respect to oxidative DNA damage, ROS and products of lipid peroxidation can have an effect on genomic and mitochondrial DNA, leading to various types of DNA damage ( 35 , 36 ). The replication of damaged DNA prior to repair results in DNA mutations and genomic instability, subsequently leading to a variety of disorders and tumorigenesis.…”
Section: Basic Ways Os Causes Cell Injurymentioning
confidence: 99%